1,3-butadiene synthesis catalyst and method for producing same, and method for producing 1,3-butadiene

JP7668884B2Active Publication Date: 2025-04-25TOYO TIRE CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023537866
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-29
Publication Date
2025-04-25
Estimated Expiration
2041-07-29

AI Technical Summary

Technical Problem

Current methods for synthesizing 1,3-butadiene from ethanol using conventional catalysts result in low yield, necessitating the development of a more efficient catalyst that can promote dehydrogenation, aldol condensation, and MPV reduction while minimizing by-product generation.

Method used

A catalyst comprising a porous silica carrier with ZnO and Zr supported on crystalline silica, where Zr interacts with silanol groups to form Lewis active centers, is used for the direct conversion of ethanol to 1,3-butadiene, employing a hydrothermal synthesis method to create micropores and optimize the molar ratios of Zn/Si and Zr/Si for enhanced performance.

Benefits of technology

The catalyst significantly improves the conversion rate and yield of 1,3-butadiene, outperforming comparative examples, with the silica carrier's MFI-type structure and specific molar ratios of Zn/Si and Zr/Si enhancing the dehydrogenation and condensation processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000010_0000
    Figure 00000010_0000
  • Figure 00000011_0000
    Figure 00000011_0000
  • Figure 00000012_0000
    Figure 00000012_0000
Patent Text Reader

Abstract

A catalyst according to one embodiment of the present invention is used for the purpose of synthesizing 1,3-butadiene from ethanol. This catalyst comprises: a porous silica carrier that is formed of crystalline silica; ZnO that is supported by the silica carrier; and Zr that has interacted with a silanol group of the silica carrier.
Need to check novelty before this filing date? Find Prior Art

Description

1,3-butadiene synthesis catalyst, its production method, and 1,3-butadiene production method

[0001] An embodiment of the present invention relates to a catalyst for synthesizing 1,3-butadiene from ethanol, a method for producing the catalyst, and a method for producing 1,3-butadiene using the catalyst.

[0002] 1,3-Butadiene is widely used as a raw material in the production of butadiene rubber (BR) and styrene-butadiene rubber (SBR). Currently, 1,3-butadiene is mainly produced by separating it from the C4 fraction during the production of ethylene by steam cracking naphtha. In recent years, there has been a demand for the synthesis of 1,3-butadiene from raw materials other than petroleum. As such an alternative method, a method for synthesizing 1,3-butadiene from ethanol by direct conversion has been proposed.

[0003] For example, Patent Document 1 discloses a catalyst for obtaining butadiene by contacting YO with ethanol. 2 and a catalyst comprising a zeolite material having a framework structure comprising: wherein at least a portion of Y contained in the framework structure is isomorphously substituted with element X. Here, Y is preferably Si, Sn, Ti, Zr, or Ge, and X is preferably Zr, Ti, Sn, or Ta. Patent Document 1 also discloses that a zeolite material in which Y is Si and X is Ti may further contain Zn as a non-framework element.

[0004] Patent Document 2 describes a catalyst for obtaining 1,3-butadiene from ethanol, which is obtained by kneading magnesium hydroxide, colloidal silica, zinc nitrate, and zirconium oxynitrate together with water and calcining the mixture (ZnO / ZrO 2 / MgO / SiO 2 ) has been disclosed.

[0005] WO2014 / 198901A1 WO2013 / 125389A1

[0006] The direct conversion of ethanol to 1,3-butadiene is a promising route. However, this direct conversion is a complex reaction and requires a multifunctional catalyst with dehydrogenation sites, Lewis acid sites, and mild Brønsted sites. However, conventional catalysts do not necessarily produce high yields of 1,3-butadiene, and there is a need to improve the yield.

[0007] An object of an embodiment of the present invention is to provide a catalyst for synthesizing 1,3-butadiene that can efficiently synthesize 1,3-butadiene from ethanol, a method for producing the same, and a method for producing ethanol using the catalyst.

[0008] The present invention includes the following embodiments: [1] A catalyst for synthesizing 1,3-butadiene from ethanol, the catalyst comprising: a porous silica support made of crystalline silica, ZnO supported on the silica support, and Zr interacting with a silanol group of the silica support.

[0009] [2] A method for producing 1,3-butadiene, comprising obtaining 1,3-butadiene from ethanol in the presence of a catalyst comprising a porous silica support made of crystalline silica, ZnO supported on the silica support, and Zr interacting with a silanol group of the silica support.

[0010] [3] In the above [1] or [2], the catalyst has micropores with a pore diameter of 2 nm or less.

[0011] [4] In any one of the above [1] to [3], the catalyst has an MFI-type framework structure.

[0012] [5] In any one of the above [1] to [4], the catalyst has a molar ratio of Zn to Si, Zn / Si, of 0.001 to 0.1, and a molar ratio of Zr to Si, Zr / Si, of 0.05 to 0.5.

[0013] [6] In any one of the above [1] to [5], the catalyst is a catalyst obtained by mixing a zinc salt, a zirconium alkoxide, an orthosilicate ester, and a template agent together with water, followed by hydrothermal synthesis and calcination.

[0014] [7] In the above [6], the template agent is tetrapropylammonium hydroxide.

[0015] [8] A method for producing a catalyst for synthesizing 1,3-butadiene from ethanol, the method comprising: (i) mixing a zinc salt, a zirconium alkoxide, an orthosilicate ester, and a template agent together with water; (ii) performing hydrothermal synthesis using the mixture obtained; and (iii) calcining the reaction product obtained by the hydrothermal synthesis.

[0016] [9] In the above [8], the template agent is tetrapropylammonium hydroxide.

[0017] According to an embodiment of the present invention, 1,3-butadiene can be efficiently synthesized from ethanol.

[0018] Zn 2p spectra of the ZnZrMFI catalyst of Example 1 and pure ZnO 2 Graph showing XRD measurement results of the ZnZrMFI catalyst of Example 1 Schematic diagram of the reactor used in the examples

[0019] The catalyst for synthesizing 1,3-butadiene according to this embodiment (hereinafter, sometimes simply referred to as the catalyst) and the method for producing 1,3-butadiene using the catalyst will be described below.

[0020] [Catalyst for synthesizing 1,3-butadiene] The catalyst according to the embodiment is a catalyst for synthesizing 1,3-butadiene from ethanol, and contains a porous silica support, Zn, and Zr.

[0021] Silica carriers are made of crystalline silica and are porous crystals with a three-dimensional pore structure. Therefore, compared to amorphous silica, they have a larger specific surface area, which is advantageous for dispersing various active centers and can improve catalytic performance. Pores include micropores, mesopores, and macropores, and silica carriers may have only one of these types or two or more types. In this specification, micropores refer to pores with a pore diameter of 2 nm or less. Mesopores refer to pores with a pore diameter of more than 2 nm and less than 50 nm. Macropores refer to pores with a pore diameter of 50 nm or more.

[0022] The silica support is SiO 2 The skeleton structure basically contains SiO 2 However, a part of the Si contained in the framework structure may be substituted with a trivalent, tetravalent and / or pentavalent element such as aluminum. Preferably, the silica support is SiO 2 In one embodiment, the silica support may be a zeolite that does not contain aluminum element (i.e., a dealuminated zeolite).

[0023] The skeletal structure of the silica carrier is not particularly limited, and examples thereof include MFI type, BEA type, FER type, MWW type, MOR type, FAU type, LTA type, LTL type, etc., and the silica carrier may have a skeletal structure of any one of these or a combination of two or more of these. Among these, the silica carrier in one embodiment preferably has an MFI type skeletal structure.

[0024] In the catalyst, zinc (Zn) is supported on the silica support in the form of an oxide, i.e., ZnO. Because the atomic radius of Zn is larger than that of Si, Zn does not enter the framework of the silica support during the catalyst synthesis process, and is supported on the silica support in the form of an oxide. It is believed that the ZnO supported on the silica support primarily promotes the dehydrogenation of ethanol.

[0025] In the above catalyst, zirconium (Zr) is contained in a state where it mainly interacts with the silanol groups (Si-OH) of the silica support. Because the atomic radius of Zr is larger than that of Si, Zr does not enter the framework structure of the silica support during the catalyst synthesis process, and instead interacts with Zr and SiO 2 The silanol groups on the surface interact with Zr to form Lewis active centers. Here, the interaction between the silanol groups and Zr means that some kind of bond is formed between the silanol groups and Zr. Specifically, it is preferable that Zr is coordinated to the silanol groups, and Zr forms a Si-O-Zr bond together with the Si of the silanol groups, for example, in the form shown in the following formula (1), i.e., Zr(OH)(OSi) 3 You can also take.

[0026] In the above catalyst, Zr may be only one that has interacted with the silanol group in this way, but some Zr may be in the form of an oxide, i.e., ZrO 2 In one embodiment of the catalyst, Zr may be supported on a silica support in the form of Zr(OH)(OSi) 3 and ZrO 2 It may be included in the form of

[0027] The catalyst according to this embodiment has at least one type of pore selected from the group consisting of micropores, mesopores, and macropores, since the silica support is made of porous silica as described above. In one embodiment, the catalyst preferably has micropores with a pore diameter of 2 nm or less. In this case, the catalyst may have mesopores and / or macropores in addition to the micropores. The pore diameter of the micropores, as measured by the HK method, is not particularly limited, but is preferably 0.3 nm to 1.5 nm, more preferably 0.5 nm to 1.0 nm.

[0028] In the above catalyst, the molar ratio of zinc to silica, Zn / Si, is not particularly limited, but is preferably 0.001 to 0.1. A molar ratio of Zn / Si of 0.001 or more can enhance the effect of promoting ethanol dehydrogenation. A molar ratio of Zn / Si of 0.1 or less can promote ethanol dehydrogenation without inhibiting the activity of other active species. The molar ratio Zn / Si is preferably 0.005 or more, more preferably 0.008 or more. Furthermore, the molar ratio Zn / Si is preferably 0.05 or less, more preferably 0.03 or less.

[0029] In the catalyst, the molar ratio Zr / Si of zirconium element to silica element is not particularly limited, but is preferably 0.05 to 0.5. When the molar ratio Zr / Si is 0.05 or more, the effect of promoting aldol condensation and MPV reduction can be enhanced. When the molar ratio Zr / Si is 0.5 or less, the generation of by-products can be suppressed. The molar ratio Zr / Si is preferably 0.08 or more, more preferably 0.1 or more. Furthermore, the molar ratio Zr / Si is preferably 0.4 or less, more preferably 0.3 or less.

[0030] [Method for Producing Catalyst for 1,3-Butadiene Synthesis] The method for producing the catalyst is not particularly limited, but it is preferable to prepare the catalyst by hydrothermal synthesis.

[0031] A preferred embodiment of the production method using hydrothermal synthesis includes the following steps: (i) mixing a zinc salt, a zirconium alkoxide, an orthosilicate ester, and a template agent together with water, (ii) performing hydrothermal synthesis using the resulting mixture, and (iii) calcining the reaction product obtained by the hydrothermal synthesis.

[0032] The zinc salt is not particularly limited, and examples thereof include water-soluble zinc salts such as zinc acetate, zinc nitrate, zinc sulfate, zinc chloride, and zinc bromide, and these may be used alone or in combination of two or more.

[0033] The zirconium alkoxide is not particularly limited, and examples thereof include zirconium methoxide, zirconium ethoxide, zirconium propoxide, and zirconium butoxide, and these may be used alone or in combination of two or more.

[0034] The template agent is not particularly limited, but it is preferable to use, for example, tetrapropylammonium hydroxide (TPAOH).

[0035] Examples of orthosilicate esters as silica sources include tetraethoxysilane (TEOS), tetramethoxysilane (TEMOS), tetrapropoxysilane, and tetrabutoxysilane, and these may be used alone or in combination of two or more.

[0036] The amount of zinc salt used is not particularly limited, but the molar ratio of zinc element to silicon element, Zn / Si, relative to the amount of orthosilicate ester used is preferably 0.001 to 0.1, more preferably 0.005 to 0.05, and even more preferably 0.008 to 0.03.

[0037] The amount of zirconium alkoxide used is not particularly limited, but the molar ratio Zr / Si of zirconium element to silicon element relative to the amount of orthosilicate ester used is preferably 0.05 to 0.5, more preferably 0.08 to 0.4, and even more preferably 0.1 to 0.3.

[0038] The amount of the template agent used is not particularly limited, but may be 20 to 200 parts by mass, 50 to 150 parts by mass, or 80 to 120 parts by mass relative to 100 parts by mass of the orthosilicate ester used.

[0039] In step (i), when the zinc salt, zirconium alkoxide, orthosilicate ester, template agent and water are mixed, other components such as a lower alcohol may be included.

[0040] Specifically, in step (i), a zinc salt, a zirconium alkoxide, and an orthosilicate ester may be dissolved in a lower alcohol such as ethanol, and the resulting solution may be mixed with a template agent and water. In this way, in the presence of the zinc salt and the template agent, the orthosilicate ester undergoes hydrolysis and dehydration condensation, and the zirconium alkoxide also undergoes hydrolysis, resulting in interaction between Zr and silanol groups.

[0041] In step (i), the lower alcohol may be distilled off from the mixture containing the ZnZr silicate precursor thus obtained.

[0042] Next, in step (ii), the mixture is subjected to hydrothermal synthesis. Hydrothermal synthesis is a reaction carried out in the presence of high-temperature, high-pressure hot water, where further dehydration condensation occurs to produce silica. The presence of a template agent during this process forms pores with a specified pore size. Furthermore, since zinc salt and zirconium alkoxide are mixed with an orthosilicate ester to perform one-pot hydrothermal synthesis, the active centers Zn and Zr can be uniformly dispersed on the silica support, promoting interaction between the active centers.

[0043] The hydrothermal synthesis can be carried out, for example, using an autoclave. The treatment conditions are not particularly limited, but may be, for example, at 150 to 180°C, under pressure spontaneously generated by volume expansion, for 24 to 96 hours.

[0044] After the hydrothermal synthesis, the resulting reaction product is dried, and then in step (iii), the reaction product is calcined. This results in a catalyst according to one embodiment. The calcination temperature is not particularly limited and may be, for example, 300 to 700°C or 400 to 600°C. After calcination, the product may be crushed and further molded, such as by sieving, if necessary.

[0045] [Method for Producing 1,3-Butadiene] The method for producing 1,3-butadiene according to this embodiment includes obtaining 1,3-butadiene from ethanol in the presence of the catalyst according to this embodiment described above. To achieve this, a raw material containing ethanol is brought into contact with the catalyst.

[0046] The synthetic pathway from ethanol to 1,3-butadiene using this catalyst is not particularly limited, but is generally believed to proceed as follows: (1) ethanol is dehydrogenated to acetaldehyde, (2) acetaldehyde is converted to acetaldol by aldol condensation, (3) acetaldol is converted to crotonaldehyde by dehydration, (4) crotonaldehyde is reduced together with ethanol by MPV reduction to crotyl alcohol, and (5) crotyl alcohol is dehydrated to 1,3-butadiene.

[0047] The ethanol used in the production is not particularly limited, and may be, for example, bioethanol produced from biomass or ethanol synthesized by the hydration reaction of ethylene derived from fossil fuels. The raw material may contain other components such as acetaldehyde in addition to ethanol.

[0048] The method for contacting the ethanol-containing raw material with the catalyst is not particularly limited as long as it is a method that can convert ethanol into 1,3-butadiene in the presence of the catalyst, and may be carried out in a gas phase or a liquid phase. Preferably, the ethanol-containing raw material is made into a gas and the gas is passed through a catalyst bed containing the catalyst to carry out the reaction in the gas phase.

[0049] When the reaction is carried out in a gas phase, the raw material gas may be supplied to the reaction system without dilution, or may be supplied after being diluted with an inert gas such as nitrogen or argon.

[0050] The reaction temperature (temperature of the catalyst bed) is not particularly limited as long as it is a temperature at which ethanol can be converted into 1,3-butadiene, and may be, for example, 250 to 500° C. or 300 to 400° C. The reaction pressure is also not particularly limited, and may be, for example, atmospheric pressure to 1 MPa.

[0051] The reaction method may be a continuous flow method or a batch method. In the case of a continuous flow method, the weight hourly space velocity (WHSV), which is the ratio of the raw material supply rate (weight / hour) to the catalyst weight, is not particularly limited, and may be, for example, 0.1 to 10 h -1 Or 0.3 to 2 hours -1 That's fine too.

[0052] The reaction system is not particularly limited and may be any of a fixed bed system, a moving bed system, and a fluidized bed system. The type of reactor is also not particularly limited and, for example, a tubular reactor can be used.

[0053] The product obtained after the reaction may be purified by distillation or the like, if necessary, to remove unreacted ethanol and by-products such as ethylene, ether, and acetaldehyde.

[0054] Examples will be shown below, but the present invention is not limited to these examples.

[0055] [Method of Measuring Pore Diameter] Using a catalyst as a sample, a measurement device "3Flex 2MP" ​​manufactured by Micromeritics was used to measure the pore diameter. 2 ) Adsorption and desorption measurements were performed. Prior to the measurements, the samples were degassed under vacuum at 350°C for 5 hours. This measurement device analyzes the pore size distribution of micropores using the HK method and the pore size distribution of mesopores and macropores using the BJH method. The pore size distribution of the log differential pore volume distribution (dV / dlogD) was determined by the measurements, and the peak pore size was calculated from the obtained pore size distribution.

[0056] Example 1: Preparation of ZnZrMFI catalyst. In 10 mL of ethanol, 0.05 g of zinc acetate (Zn(CH 3 COO) 2 ・2H 2 0) and 5.21 g of tetraethoxysilane (TEOS) were added and stirred for 1 hour to dissolve. 2.40 g of zirconium butoxide (Zr(OBu) 4 After adding 100g of ZnZrMFI catalyst (molar ratio Zn / Si = 0.01, molar ratio Zr / Si = 0.2), 5.08g of tetrapropylammonium hydroxide (TPAOH) and 18.69g of water were added and stirred for 4 hours. The resulting mixture was heated at 90°C for 4 hours to remove ethanol, and then transferred to a stainless steel autoclave lined with fluororesin. Hydrothermal synthesis was carried out at 130°C for 48 hours at a pressure that spontaneously developed due to volume expansion. The resulting reaction product was dried at 100°C for 12 hours and then calcined in air at 550°C for 5 hours to obtain a ZnZrMFI catalyst (molar ratio Zn / Si = 0.01, molar ratio Zr / Si = 0.2).

[0057] The resulting ZnZrMFI catalyst had a peak pore diameter of 0.54 nm and contained micropores.

[0058] The ZnZrMFI catalyst was analyzed by X-ray photoelectron spectroscopy (XPS) using an "ESCALAB 250 Crossy" instrument manufactured by Thermo Fisher Scientific with an AlKa X-ray source. This resulted in the Zn 2p spectrum shown in Figure 1 and the Zr 3d spectrum shown in Figure 2. Furthermore, the ZnZrMFI catalyst was analyzed for its crystal structure using X-ray diffraction (XRD) (CuKα 40 kV, 20 mA, 6°-60°), and the measurement results shown in Figure 3 were obtained.

[0059] Regarding the binding energy of the Zr 3d peak shown in Figure 2, pure ZrO 2 Two peaks were observed in the ZnZrMFI catalyst (Zn 0.01 Zr 0.2 MFI(mi)) is pure ZrO 2 The binding energy of the Zr 3d peak is higher than that of ZrO 2 It can be seen that a chemical species other than the pure ZrO was formed. The two peaks of the ZnZrMFI catalyst can be divided into two main peaks and two weaker peaks, as shown in Figure 2. 2 The two weak peaks that match the binding energy of ZrO 2 The two main peaks shifted to higher energy correspond to Si—O—Zr.

[0060] On the other hand, the binding energy of the Zn 2p peak shown in Figure 1 is 0.01 Zr 0.2 MFI(mi) showed no obvious change in the peak compared to pure ZnO, indicating that it exists in the form of ZnO.

[0061] As shown in FIG. 3, the ZnZrMFI catalyst (Zn 0.01 Zr 0.2 MFI(mi)) has a peak characteristic of MFI indicated by an "x".

[0062] From the above, the prepared ZnZrMFI catalyst contains a silica support having an MFI-type framework structure, in which Zn is supported on the silica support in the form of ZnO and Zr is supported in the form of Zr(OH)(OSi). 3 and ZrO 2 It can be seen that it is included in the form of

[0063] Comparative Example 1: Preparation of ZnCe / beta catalyst 100 mL of 13 mol / L nitric acid was added to 5.0 g of H-beta (Tosoh Corporation's "941HOA"), and the mixture was stirred at 100°C for 12 hours, filtered, and washed to obtain Si-beta. 5 g of Si-beta and 0.96 g of Zn(NO 3 ) 2 ・6H 2 O and 0.66 g of Ce(NO 3 ) 3 ・6H 2 O was mixed and finely pulverized, and then calcined in air at 500° C. for 6 hours, thereby obtaining a ZnCe / beta catalyst (Zn content=5.0 mass %, Ce content=5.0 mass %).

[0064] Comparative Example 2: Preparation of ZrMFI catalyst 1.91 g of cetyltrimethylammonium bromide (CTAB) was dissolved in 300 mL of deionized water with stirring to obtain solution A. 2.60 g of TEOS and 2.40 g of Zr(OBu) were added. 4 was mixed with 10 mL of ethanol under stirring to obtain solution B. Solution B was slowly added to solution A with stirring and aged overnight. The solid product was centrifuged at 2500 rpm and dried at 60°C overnight to obtain a zirconium silicate precursor.

[0065] A mixed solution was prepared by adding 2.60 g of TEOS to 10 mL of ethanol. The zirconium silicate precursor was added to the mixed solution and stirred for 1 hour. Next, 5.08 g of TPAOH and 18.69 g of H 2The mixture was stirred at 700 rpm for 4 hours and then heated at 90°C for 4 hours to remove most of the water and ethanol from the mixture. After forming a gel, it was mixed with 2.30 g of glycerol and then transferred to a fluororesin-lined stainless steel autoclave for hydrothermal synthesis at 130°C for 48 hours. The product was dried at 100°C for 12 hours and then calcined in air at 550°C for 5 hours to obtain Zr. 0.2 An MFI catalyst was obtained.

[0066] [Catalytic Performance Evaluation Test] Each of the catalysts prepared above was subjected to a catalytic performance evaluation test in a synthesis reaction of 1,3-butadiene from ethanol. The synthesis reaction was carried out under atmospheric pressure using a quartz fixed-bed flow reactor with an inner diameter of 4 mm.

[0067] A conceptual diagram of the reaction apparatus is shown in Figure 4. In Figure 4, reference numeral 12 denotes a nitrogen cylinder that supplies nitrogen as a carrier gas, reference numeral 14 denotes a syringe pump that supplies ethanol, reference numeral 16 denotes a mass flow controller (MFC), reference numeral 18 denotes an evaporator, and reference numeral 20 denotes a ribbon heater as a line heater that heats the outer periphery of a pipe through which the gas flows.

[0068] Reference numeral 22 denotes a fixed-bed flow-type reactor, reference numeral 24 denotes a catalyst bed in the reactor 22, reference numeral 26 denotes an electric furnace that heats the reactor 22, and reference numeral 28 denotes a thermocouple thermometer (TC) that detects the temperature of the catalyst bed 24.

[0069] Reference numeral 30 denotes a pipe through which gas that has passed through the reactor 22 flows, reference numeral 32 denotes a bypass route that bypasses the reactor 22, reference numeral 34 denotes a gas chromatograph (GC) for analyzing the gas product, reference numeral 36 denotes an exhaust gas outlet, and reference numeral 38 denotes a six-way valve for switching the flow path for the above-mentioned pipe 30, bypass route 32, GC 34, and exhaust gas outlet 36.

[0070] The reactor 22 was filled with 0.5 g of catalyst to form a catalyst bed 24, and quartz wool 40 was packed and fixed on both sides of the catalyst bed 24. Nitrogen was flowed into the reactor 22 from the nitrogen cylinder 12 via the MFC 16 at a flow rate of 20 mL / min, and the reactor was pretreated at 400°C for 1 hour. After cooling to 350°C, ethanol was introduced into the reaction system using the syringe pump 14 at a rate of 0.24 mL / h (diluted by flowing nitrogen as a carrier gas at 20 mL / min) (WHSV = 0.38 h). -1 The catalyst was evaluated for 6 hours.

[0071] On-line, the gas product discharged from the reactor 22 was introduced into a gas chromatograph (GC) 34, and the gas product was analyzed using a gas chromatograph (Shimadzu GC-14B manufactured by Shimadzu Corporation and DB-1 column (30 m × 0.25 mm × 0.25 μm) manufactured by GL Sciences) and a flame ionization detector (FID).

[0072] The formulas for calculating the conversion rate (ethanol conversion rate), the selectivity of each product, and the yield (yield of 1,3-butadiene) are shown below.

[0073]

[0074] The results are shown in Table 1, and 1,3-butadiene, ethylene, acetaldehyde, diethyl ether, and other coupling products were detected. The catalyst of Example 1 had a significantly higher ethanol conversion rate and the highest 1,3-butadiene yield compared to the catalysts of Comparative Examples 1 and 2. Therefore, efficient synthesis of 1,3-butadiene was possible.

[0075] The various numerical ranges described in this specification can be arbitrarily combined with their respective upper and lower limit values, and all such combinations are considered to be preferred numerical ranges described in this specification. Furthermore, a numerical range described as "X to Y" means from X to Y.

[0076] Although several embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their omissions, substitutions, modifications, etc. are included within the scope and spirit of the invention, as well as within the scope of the invention described in the claims and their equivalents.

Claims

1. A catalyst for synthesizing 1,3-butadiene from ethanol, comprising: a porous silica support made of crystalline silica; ZnO supported on the silica support; and Zr interacting with the silanol groups of the silica support.

2. The catalyst for synthesizing 1,3-butadiene according to claim 1, which has micropores with a pore diameter of 2 nm or less.

3. The catalyst for synthesizing 1,3-butadiene according to claim 1 or 2, wherein the silica support has an MFI-type framework structure.

4. A catalyst for synthesizing 1,3-butadiene according to any one of claims 1 to 3, wherein the molar ratio of Zn to Si, Zn / Si, is 0.001 to 0.1, and the molar ratio of Zr to Si, Zr / Si, is 0.05 to 0.

5.

5. The catalyst for synthesizing 1,3-butadiene according to any one of claims 1 to 4, which is obtained by mixing a zinc salt, a zirconium alkoxide, an orthosilicate ester, and a template agent together with water, followed by hydrothermal synthesis and calcination.

6. The catalyst for synthesizing 1,3-butadiene according to claim 5, wherein the template agent is tetrapropylammonium hydroxide.

7. A method for producing 1,3-butadiene, comprising obtaining 1,3-butadiene from ethanol in the presence of a catalyst comprising a porous silica support made of crystalline silica, ZnO supported on the silica support, and Zr interacting with silanol groups of the silica support.

8. The method for producing 1,3-butadiene according to claim 7, wherein the catalyst has micropores with a pore size of 2 nm or less.

9. The method for producing 1,3-butadiene according to claim 7 or 8, wherein the catalyst has a silica support having an MFI-type framework structure.

10. A method for producing 1,3-butadiene according to any one of claims 7 to 9, wherein the catalyst has a molar ratio of Zn to Si, Zn / Si, of 0.001 to 0.1, and a molar ratio of Zr to Si, Zr / Si, of 0.05 to 0.

5.

11. A method for producing a catalyst for synthesizing 1,3-butadiene from ethanol, the method comprising: mixing a zinc salt, a zirconium alkoxide, an orthosilicate ester, and a template agent together with water; performing hydrothermal synthesis using the resulting mixture; and calcining the reaction product obtained by the hydrothermal synthesis.

12. The method for producing a catalyst for synthesizing 1,3-butadiene according to claim 11, wherein the template agent is tetrapropylammonium hydroxide.